Modeling Ice Passage through Submergible and Non-Submergible Tainter Gates - Gooch, Gordon; Rand, John; Hanamoto, Ben; Zufelt, Jon (1990)
In the cold regions of the U.S., ice accumulation in the approach area of navigation locks has been a constant problem. This ice is often pushed into the lock ahead of a towboat, sometimes requiring a separate lock cycle. This reduces the efficiency of the lock and slows down ship traffic. By modeling this problem this problem and testing the solution to it, the research team has been able to conclusively show that submergible tainter gates located near the approach will solve the above-mentioned ice problems.